2003
DOI: 10.1056/nejmoa035162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ximelagatran with Warfarin for the Prevention of Venous Thromboembolism after Total Knee Replacement

Abstract: The efficacy of oral ximelagatran, administered starting the morning after total knee replacement, was superior to that of warfarin for prevention of venous thromboembolism. Rates of hemorrhagic complications with the two drugs were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(106 citation statements)
references
References 30 publications
1
105
0
Order By: Relevance
“…In the PEGASUS trial, which included 2,048 patients undergoing high-risk abdominal surgery, postoperative fondaparinux (2.5 mg once daily) was shown to be as effective and as safe as perioperative dalteparin (5,000 IU once daily). 36 Ximelagatran, an orally administered direct thrombin inhibitor, has shown promise as a prophylactic agent in orthopedic 37 and abdominal 38 surgery based on preliminary results, but it was refused approval by the FDA in September 2004 because of concerns about liver toxicity. 39 The company has withdrawn the substance but other thrombin inhibitors are on the way.…”
Section: Pharmacologic Prophylaxismentioning
confidence: 99%
“…In the PEGASUS trial, which included 2,048 patients undergoing high-risk abdominal surgery, postoperative fondaparinux (2.5 mg once daily) was shown to be as effective and as safe as perioperative dalteparin (5,000 IU once daily). 36 Ximelagatran, an orally administered direct thrombin inhibitor, has shown promise as a prophylactic agent in orthopedic 37 and abdominal 38 surgery based on preliminary results, but it was refused approval by the FDA in September 2004 because of concerns about liver toxicity. 39 The company has withdrawn the substance but other thrombin inhibitors are on the way.…”
Section: Pharmacologic Prophylaxismentioning
confidence: 99%
“…Although clinical trials showed that ximelagatran, the first oral direct thrombin inhibitor to be developed, is an effective anticoagulant for many clinical indications [19][20][21][22], it was withdrawn from the market by the manufacturer in February 2006 [23] because of fears of liver toxicity. There are, however, other direct thrombin inhibitors that are under development and will appear in its wake.…”
Section: Discussionmentioning
confidence: 99%
“…Dependence on AT to achieve an anticoagulant effect has been overcome, however, by the development of direct thrombin inhibitors (DTIs). One such agent is the novel oral DTI ximelagatran, which is currently undergoing clinical evaluation for the prevention and treatment of thromboembolic disorders [25][26][27]. Following oral administration, ximelagatran is rapidly absorbed and bioconverted to its active form melagatran which, unlike UH and low-molecular-weight heparin (LMWH), provides competitive, direct inhibition of both free and clot-bound thrombin [12,28].…”
Section: Discussionmentioning
confidence: 99%